Checklist of Helminth parasites of Amphibians from South America - Campião, Karla Magalhães; Morais, Drausio Honorio; Dias, Olívia Tavares; Aguiar, Aline; Toledo, Gislayne; Tavares, Luiz Eduardo Roland; Da Silva, Reinaldo José (Zootaxa, 2014)
Parasitological studies on helminths of amphibians in South America have increased in the past few years. Here, we present a list with summarized data published on helminths of South American amphibians from 1925 to 2012, including a list of helminth parasites, host species, and geographic records. We found 194 reports of helminths parasitizing 185 amphibian species from eleven countries: Argentina, Brazil, Chile, Colombia, Equador, French Guyana, Guyana, Paraguay, Peru, Uruguay and Venezuela. Helminth biodiversity includes 278 parasite species of the groups Acanthocephala, Nematoda, Cestoda, Monogenea and Trematoda. A list of helminth parasite species per host, and references are also presented. This contribution aims to document the biodiversity of helminth parasites in South American amphibians, as well as identify gaps in our knowledge, which in turn may guide subsequent studies.